DEVELOPMENT OF A PROGRAM FOR CONDUCTING TESTS WITH PHYSICAL SAMPLES OF A DEFENCE INDUSTRY PRODUCT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The developed Program for Conducting a Test with Physical Samples of a Defence Industry Product is a systematic approach to scientific research related to the study, research, and collection of various types of data (information) on the researched object. The constructed and subjected to testing physical samples (models) of the product are used to confirm the correctness of the initial assumptions made. They are related to the possibility of improving the final product without changing the basic requirements for it. The search for an appropriate solution to the research task is related to the construction and testing of a new type of details. They are related to the accumulation of reliable spatial-geometrical data about the product and its reliability characteristics. In addition, to improve the visual perception of the physical objects, a Visual 3D model of the tested physical samples of a chemical power source (batteries) was developed and presented in the report using the capabilities of modern digital programs.